Helminth Parasites of the Juvenile Hawksbill Turtle Eretmochelys imbricata (Testudines: Cheloniidae) in Brazil - Werneck, M. R.; Lima, E. H.S.M.; Pires, T.; Silva, R. J. [UNESP] (American Society of Parasitologists, 2015)
The helminth fauna of 31 juvenile specimens of Eretmochelys imbricata from the Brazilian coast was examined. Seventeen individuals were infected with helminths (54.8%). The helminths found were: Diaschistorchis pandus, Cricocephalus albus, Metacetabulum invaginatum, Pronocephalus obliquus (Pronocephalidae), Cymatocarpus solearis (Brachycoeliidae), Styphlotrema solitaria (Styphlotrematidae), Carettacola stunkardi, Amphiorchis caborojoensis (Spirorchiidae), Orchidasma amphiorchis (Telorchiidae), and Anisakis nematode larvae. This report is the first analysis of parasite communities in this host.